ANALISIS TINGKAT KESUKAAN KONSUMEN TERHADAP NUGGET BELUT (Monopterus albus) DENGAN PENAMBAHAN TAPIOKA DAN PATI SAGU - BUNGA RIA YULIANA SIAHAAN; FAJAR RESTUHADI; EVY ROSSI (Universitas Riau, 2016)
This research was carried out for to see the addition of tapioca and sago starch nutrient content nuggetaccording to SNI 01-6683-2002 and see the characteristics of sensory attributes preferred by consumers andget the best position for five products nugget from the consumer side. This study was conducted experimentswith five treatments and three replications. The combination of these treatments is TSB1 (15% tapioca, sago0%), TSB2 (10% tapioca, sago 5%), TSB3 (7,5% tapioca, sago 7,5%), TSB4 (5% tapioca, sago 10 %) andTSB5 (0% tapioca, sago 15%). Sensory analysis was performed hedonic test (consumer acceptance) anddescriptive test. The addition of tapioca and sago starch in the manufacture nugget eel meet the qualityrequirements contained in SNI 01-6683-2002 as the water content is 36,76-38,49%; protein 13,54-13,98%fat and 16,93-17,38%. However, the carbohydrate content has not fulfilled SNI namely 28,64-30,20% andash content was obtained 1,95-2,12% of unknown quality standard in SNI 01-6683-2002. The level ofconsumer preferences towards nuggets eel preferred by preference mapping is treated TSB1 (tapioca 15%;sago 0%) and TSB2 (tapioca 10%; sago 5%) with the quality attributes of texture (hardness), taste pepper,brown color and flavor sweet nuggets while most preferred is the treatment TSB3 (tapioca 7,5%; sago 7,5%)with the quality attributes onion aroma, the smell of garlic, pepper aroma, the scent of fish, fish flavor, garlicflavor and taste of onion.